Respiratory eukaryotic virome expansion and bacteriophage deficiency characterize childhood asthma - Megremis Spyridon; Constantinides Bede; Xepapadaki Paraskevi; Yap Chuan Fu; Sotiropoulos Alexandros G; Bachert Claus; Finotto Susetta; Jartti Tuomas; Tapinos Avraam; Vuorinen Tytti; Andreakos Evangelos; Robertson David L; et al. (Nature Publishing Group, 2025)
Asthma development and exacerbation is linked to respiratory virus infections. There is limited information regarding the presence of viruses during non-exacerbation/infection periods. We investigated the nasopharyngeal/nasal virome during a period of asymptomatic state, in a subset of 21 healthy and 35 asthmatic preschool children from the Predicta cohort. Using metagenomics, we described the virome ecology and the cross-species interactions within the microbiome. The virome was dominated by eukaryotic viruses, while prokaryotic viruses (bacteriophages) were independently observed with low abundance. Rhinovirus B species consistently dominated the virome in asthma. Anelloviridae were the most abundant and rich family in both health and asthma. However, their richness and alpha diversity were increased in asthma, along with the co-occurrence of different Anellovirus genera. Bacteriophages were richer and more diverse in healthy individuals. Unsupervised clustering identified three virome profiles that were correlated to asthma severity and control and were independent of treatment, suggesting a link between the respiratory virome and asthma. Finally, we observed different cross-species ecological associations in the healthy versus the asthmatic virus-bacterial interactome, and an expanded interactome of eukaryotic viruses in asthma. Upper respiratory virome "dysbiosis" appears to be a novel feature of pre-school asthma during asymptomatic/non-infectious states and merits further investigation.